سہ ماہی ”اُردو “ ارتقائی سفراور لسانی وادبی خدمات: QUARTERLY "URDU" EVOLUTIONARY JOURNEY AND LINGUISTIC LITERARY SERVICES (Al-Aasar, 2025)
This research article explores the centennial contributions of Sah-Mahi Urdu, a quarterly publication by Anjuman Taraqqi-e-Urdu, in the realms of literary, scholarly, and linguistic development. Over the past century, the journal has played a pivotal role in promoting Urdu literature by providing a platform for poetry, prose, fiction, criticism, and travelogues. It has nurtured emerging writers and encouraged innovative literary trends. Academically, the journal has published research articles and scholarly essays, offering deep insights into Urdu language, literature, history, and culture, thus enhancing scholarly standards in educational institutions. Linguistically, Sah-Mahi Urdu has contributed to the development of Urdu grammar, lexicon, and stylistics, maintaining the language's standard while adapting to contemporary needs. The study concludes that Sah-Mahi Urdu has remained an authoritative and influential reference in Urdu literary and linguistic discourse, promoting literary consciousness, academic research, and linguistic growth over its century-long journey.